Celebrating new ‘voices’ - Finlay, Linda (European Journal for Qualitative Research in Psychotherapy, 2011)
The articles in this issue are diverse in terms of their focus, style and substance. The authors, too, come from different fields of psychotherapy and they vary in their experience. What links the papers is that all the authors are all relatively new voices in our academic/research/writing world. For most, indeed, this is their first ever published paper.